2019
DOI: 10.1080/2090598x.2019.1645262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of extracorporeal shockwave lithotripsy with furosemide and hydration in renal stone management: A randomised controlled trial

Abstract: 2019) Efficacy of extracorporeal shockwave lithotripsy with furosemide and hydration in renal stone management: A randomised controlled trial, Arab Journal of Urology, 17:4, 279-284, ABSTRACT Objective: To assess the effect of diuretics (furosemide) administered before extracorporeal shockwave lithotripsy (ESWL) followed by continuous infusion of 0.9% NaCl during the ESWL in patients with renal stones. Patients and methods: A tertiary care teaching hospital-based prospective randomised controlled trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“… 13 Thus, we evaluated the complications in the remaining five studies. 9 12 , 14 No complications were observed in the Azm and Higazy 9 and Zomorrodi et al. 10 studies, whereas the remaining three studies reported complications after SWL treatment to remove RS.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 13 Thus, we evaluated the complications in the remaining five studies. 9 12 , 14 No complications were observed in the Azm and Higazy 9 and Zomorrodi et al. 10 studies, whereas the remaining three studies reported complications after SWL treatment to remove RS.…”
Section: Resultsmentioning
confidence: 92%
“…Finally, we included six RCTs that examined the synergistic action of SWL and furosemide against the actions of SWL alone. 9 14 A flowchart of our inclusion/exclusion process is presented in Figure 1 , and the demographics of the six eligible articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Azm et al 14 showed that the use of diuretics with ESWL improved stone clearance rate with the diuretic and ESWL clearance rate being 92.3% compared to 87% ESWL alone without diuretics in 106 ureteric calculi patients. A study by Sohu et al 15 in 714 patients reported a higher stone free rate in the diuretic group compared to the standard ESWL, 77% compared to 65% respectively (p < 0.001).…”
Section: Discussionmentioning
confidence: 96%
“…Diuretics increase urine flow around the stone during ESWL, 3,4 therefore, improving stone fragmentation 5 and removal. The main mechanism employed is the cavitation phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, 6 RCTs [10][11][12][13][14][15] involving 1344 patients were included in the analysis. Table 1 shows the characteristics of the individual RCTs.…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%